(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
Studies on postgraduate research students’ perceptions and experiences are highly valuable to develop supervisory policies and support mechanisms for enhancing research quality at universities. Understanding how university research students experienced learning research skills and what challenges they often faced can be insightful input for researchers and research supervisors. However, in the context of Nepal’s higher education, we find very limited studies on students’ perceptions and experiences of conducting research as a part of degree completion. This study aims to explore postgraduate research students’ lived experiences of learning research as a part of thesis writing at Nepal’s universities. Following the phenomenological approach particularly semi-structured interviews and observation, this paper reports the postgraduate students’ experiences of getting started with the research issues, collecting data from the field and receiving supervisory support from their supervisors. The major findings are reported as the delayed decision on the area of interest, lack of proper research orientation and counseling, researchers’ dilemmas during the process and vague and superficial supervisory feedback on thesis drafts. These findings might help the researchers, research students and university administrations to better understand the lived experiences of the students and develop the supervisory policies, support mechanisms and supervisory strategies at the universities.